Using Mobile Gaming in Virtual Physical Education: Challenges and Opportunities - Paolo Nino Valdez; Janet Mariano; Ma. Socorro Gigi Cordova (University of Johannesburg, 2023)
Recent research into education during the Coronavirus (COVID-19) pandemic has revealed several structural inequalities leading to problematic implementation of teaching and learning programmes globally. However, while the use of communication technology has been used to bridge the physical distance between teachers and students, certain subjects, such as Physical Education (PE), pose logistical challenges since this entails actual development of physical skills on the part of the learner. This reflective piece examines the use of mobile gaming as an alternative to traditional PE programmes. Specifically, we argue that mobile gaming helps develop peer engagement, critical thinking, and communication skills. On the other hand, challenges such as a need to engage in more physical activities, addiction, and access to technology were encountered.